Sistem Manajemen Dokumen Pada Dinas Pengelolaan Sumber Daya Air Provinsi Sumatera Selatan - Muharram, Muhammad Mukmin; Inayatullah, Inayatullah; Arman, Molavi (Jurnal Teknologi Sistem Informasi, 2023)
The Department of Water Resources Management of South Sumatra Province is the administration of government affairs in the field of public works of irrigation for the province of South Sumatra which is located on Jl. Captain Anwar Sastro, Sungai Pangeran, Kec. Ilir Team. I, Palembang City..The purpose of making this website-based document management system is to make it easier for the office to process incoming and outgoing documents, reduce the level of risk of loss, damage to incoming document data, outgoing documents, as well as reports of incoming and outgoing documents by period document. The system development methodology used is an iterative methodology, where the stages in the methodology are: planning, analysis, design, coding, and testing. Interviews and observations are the first steps taken before analyzing system requirements. Tools in data design using Entity Relationship Diagram (ERD) using visual studio software and SQL Server 2000 database. The document management system developed can improve performance, especially in document management at the Water Resources Management Office of South Sumatra Province.